2012
DOI: 10.1038/ejhg.2012.240
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variant of Brachydactyly-mental retardation syndrome in a family with an inherited interstitial 2q37.3 microdeletion including HDAC4

Abstract: Deletions of the chromosomal region 2q37 cause brachydactyly-mental retardation syndrome (BDMR), also known as Albright hereditary osteodystrophy-like syndrome. Recently, histone deacetylase 4 (HDAC4) haploinsufficiency has been postulated to be the critical genetic mechanism responsible for the main clinical characteristics of the BDMR syndrome like developmental delay and behavioural abnormalities in combination with brachydactyly type E (BDE). We report here on the first three generation familial case of BD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 21 publications
(32 reference statements)
0
41
0
2
Order By: Relevance
“…Analysis of HDAC4 expression showed it was reduced to 67% in mother and 23% in her son, compared to normal controls level of HDAC4, therefore the amount of HDAC4 correlated with the severity of the phenotype (Morris et al, 2012). Further evidence that HDAC4 is causative in BDMR arose from a three generation familial case in which three family members were found to carry a 800 kb microdeletion of 2q37.2 which included HDAC4, FLJ43879 and TWIST2, which was inherited in an autosomal dominant manner, and associated with intellectual disability, memory deficits, reduced spatial orientation and developmental delays, with variable severity (Villavicencio-Lorini et al, 2013). However, haploinsufficiency of HDAC4 does not always result in intellectual disability.…”
Section: Loss Of Hdac4 Results In Memory Deficitsmentioning
confidence: 97%
“…Analysis of HDAC4 expression showed it was reduced to 67% in mother and 23% in her son, compared to normal controls level of HDAC4, therefore the amount of HDAC4 correlated with the severity of the phenotype (Morris et al, 2012). Further evidence that HDAC4 is causative in BDMR arose from a three generation familial case in which three family members were found to carry a 800 kb microdeletion of 2q37.2 which included HDAC4, FLJ43879 and TWIST2, which was inherited in an autosomal dominant manner, and associated with intellectual disability, memory deficits, reduced spatial orientation and developmental delays, with variable severity (Villavicencio-Lorini et al, 2013). However, haploinsufficiency of HDAC4 does not always result in intellectual disability.…”
Section: Loss Of Hdac4 Results In Memory Deficitsmentioning
confidence: 97%
“…The patients' sole behavioral peculiarity is a “very friendly” disposition in all affected members and III‐1 recently developed self‐injuring behavior (skin picking). Genotype–phenotype comparisons and phenotype—2q37‐breakpoint correlations showed that clinical features are variable in ˜50% of patients (Aldred et al , ; Casas et al , ; Falk & Casas, ; Villavicencio‐Lorini et al , ). B, CHand (B) and feet (C) photographs of the affected individual II‐1 with obvious BDE of fingers and toes. DqPCR was used to reduce the critical deletion region on chromosome 2q37; genomic positions refer to human genome assembly hg19. Amplification values were normalized to the non‐affected proband I‐2.…”
Section: Resultsmentioning
confidence: 99%
“…To that end, we recently demonstrated that in Drosophila, RNA interference (RNAi)-mediated knockdown of HDAC4 in the adult brain impairs long-term memory (LTM) in the courtship suppression assay, a model of associative memory (Fitzsimons et al 2013). Similarly in humans, loss of one copy of HDAC4 correlates with brachydactyly mental retardation syndrome (BDMR), the neurological symptoms of which include intellectual disability and autism (Williams et al 2010;Morris et al 2012;Villavicencio-Lorini et al 2013), and in mice, conditional knockout of HDAC4 in the brain results in impairments in hippocampal-dependent associative LTM . Despite this growing evidence of a critical role, the mechanism(s) through which HDAC4 positively influences LTM is unknown.…”
mentioning
confidence: 99%